Spory międzynarodowe i potrzeba nowego podejścia do ich załatwiania środkami pokojowymi - Iwanejko, Marian (Wydział Prawa i Administracji UAM, 1972)
Both the present theory of international conflicts and recent development in international relations in the sphere of procedures and bases for pacific solution of international disputes call for an urgent re-examination of a number of relevant problems involved. There are three such problems the examination of which is essential to meet the necessity of a new approach to international disputes and their solution by pacific means. First of all it seems to be of primary importance to propose a new and more adequate systematization of international disputes using such criteria as they appeared to have played in practice decisive role in the originating (sources) of particular disputes their stages and possible mutations. The author proposes five such criteria which give an opportunity to systematize all disputes and show them in the light of variety of characteristic features. These criteria are as follows: a) substance of the dispute (the subject matter may be territorial or personal), b) persons meaning parties to a dispute (there may by bilateral or multilateral disputes; disputes between states, states and an organization, or between organizations etc.), c) the factor of time which may have and material significance or plays a formal and procedural role, d) the factor of the locus in the meaning of the character of circumstances (local, regional or universal) which bear upon sources of a particular dispute, and e) the factor of forum which shows whether and under what conditions a particular dispute may be discussed on the international plane or falls within the exclusive national jurisdiction. The visible decline of using existing devices and means of pacific solution of international disputes as listed in the article 33 of the Charter tends to expose the international peace to a real danger. There is therefore a further need of thorough research of present practices spontaneously and often informally developing. The author gives a number of such instances which together with some other propositions may be used as a helpful indication by drafting new devices and institutions of pacific solution of international disputes. Finally there is another problem which consists in an hypothesis that there is an intimate relation between particular types of international disputes and means best calculated to bring such disputes to an desirable end. In other words the problem put forward by the author lies in an answer to the question whether there may be found a guiding rule or set of rules which would facilitate the proper choice of particular procedure best fiting in with requirements and nature of a given dispute.
International Disputes and the Need of a New Approach of their Solution by Pacific Means